2021
DOI: 10.1111/wrr.12902
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between anemia and diabetic foot ulcers? A systematic review and meta‐analysis

Abstract: Anemia was found to be prevalent in patients with diabetes mellitus. Higher rates of anemia were reported in patients having diabetic foot ulcers (DFU). With the presence of an altered microcirculation, the potential negative effects of anemia might impede ulcer healing leading to higher rates of amputation and mortality.Medline, Embase, Scopus, CINAHL, Cochrane Library, and Google Scholar, were searched for from inception to locate relevant papers reporting any association between anemia and diabetic foot ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Previous studies proved that anemia was related to DFU risk and adverse outcomes [ 28 ]. A meta-analysis of 2895 patients showed an association between anemia and DFUs, a correlation between the severity of anemia and the severity of DFUs, and that anemia may be a predictor of amputation or death in patients with DFUs [ 29 ]. However, whether improvement of anemia can prevent the occurrence and progression of DFUs still needs to be clarified by further prospective, randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proved that anemia was related to DFU risk and adverse outcomes [ 28 ]. A meta-analysis of 2895 patients showed an association between anemia and DFUs, a correlation between the severity of anemia and the severity of DFUs, and that anemia may be a predictor of amputation or death in patients with DFUs [ 29 ]. However, whether improvement of anemia can prevent the occurrence and progression of DFUs still needs to be clarified by further prospective, randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on the correlation between anemia and DFU prognosis. A meta-analysis found that increasing anemia severity was associated with DFU severity and could serve as a predictor of amputation and mortality [ 45 ]. Retrospective cohort studies identified anemia as significantly associated with larger, deeper ulcers, more severe infections, high amputation risk, and increased mortality rates [ 46 , 47 ], while observational studies in Nigeria have found anemia to be associated with poor wound healing, amputation, and increased mortality [ 48 , 49 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…An increased weight and body mass index are known to exert pressure on plantar ulcers and are key factors delaying wound healing . The esmolol with SoC group showed significantly greater wound closure in people with characteristics that impair wound healing, including those with peripheral arterial disease, anemia, and nephropathy compared with SoC alone …”
Section: Discussionmentioning
confidence: 98%